The Swiss disease: Facts and artefacts - Yngve Abrahamsen; Roland Aeppli; Erdal Atukeren; Michael Graff; Christian Müller (ETH Zurich, KOF Swiss Economic Institute, 2003)
In their introduction to the special issue of the Review of Economic Dynamics on Great Depressions of the 20th Century (Vol. 5, 2002), Timothy J. Kehoe and Edward C. Prescott argue that in the last few years great depressions have hit two rich countries: New Zealand and Switzerland. We briefly discuss Kehoe/Prescott's definition of a great depression. Thereafter, we analyse the underlying data - time series of labour productivity for the countries under consideration - and perform sensitivity tests with respect to alternative operationalisations for Switzerland and the U.S. It is shown that with different (and arguably more appropriate) time series the impressive growth gap between the well performing U.S. and poor-performing Switzerland reduces considerably. Yet, this still does not explain the comparatively poor economic growth in Switzerland during the last decades, which is noted by many observers. Accordingly, we analyse economic performance within the comparative cross-country framework, which is now standard in the new empirical literature on the determinants of economic growth. Based on a balanced panel data set on a large sample of countries with multiple observations through time, the growth rate of labour productivity is regressed on its presumed determinants, which follow from an extended version of the neo-classical aggregate production function. This analysis departs from the standard approach by focussing on the country-specific fixed effects rather than the structural growth parameters. The results show that there is no significant deviation of Switzerland's performance from its predicted value after taking account of the explicit determinants of economic growth.
Keywords: 330; Wirtschaftswachstum; Wirtschaftskrise; Arbeitsproduktivität; Schätzung; Schweiz